Multiple Intelligences in the practice of Islamic Religious Education Learning for students at STKIP Yapis Dompu - Nurhasanah, Enung; Hanafi, Hasdar (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to explore the application of multiple intelligence theory in the learning of Islamic Religious Education (PAI). The theory developed by Howard Gardner emphasizes that human intelligence is not only limited to intellectual aspects (IQ), but also includes various dimensions such as linguistics, logical-mathematical, kinesthetic, interpersonal, intrapersonal, musical, visual-spatial, and naturalist. Through the literature study approach, this research identifies how this theory can increase the effectiveness of PAI learning by utilizing the diversity of potential intelligence of students. The results showed that the application of compound intelligence theory in PAI can create an inclusive, creative, and fun learning environment. Various learning methods, such as the use of multimedia, group work, experimental learning, and emphasis on creativity, are able to accommodate the needs of students with a variety of dominant intelligences. In addition, a holistic evaluation that includes cognitive, affective, and psychomotor aspects is the key to measuring learning success. This research also highlights the importance of the teacher's role in recognizing the tendency of student intelligence and designing appropriate learning strategies. Thus, the theory of compound intelligence not only enriches the practice of PAI learning but also encourages the development of students' potential as a whole, in accordance with holistic Islamic values.